The Effect of PBL Model and Learning Styles on Mathematical Problem-Solving and Self Esteem Abilities - Wangsit Rigusti; Heni Pujiastuti; Anwar Mutaqin (IKIP Mataram, 2020)
This study aimed at determining whether the PBL model and learning styles could influence the students' mathematical problem-solving and self-esteem abilities. This study was a quasi-experimental study, in which in include of two classes namely X MIPA 1 class (Mathematics and Natural Sciences); moreover, there were 24 students who used the PBL learning model as an experimental class and X MIPA 2 (Mathematics and Natural Sciences) that consisted of 22 students used a scientific learning model as a control class at SMAN 17 Pandeglang on the academic year of 2019/2020. In addition to the learning model, the students were also categorized based on visual, auditory, and kinesthetic learning styles. The data were collected by means of learning style questionnaires, problem-solving ability test, and self-esteem questionnaires. The data analysis was performed statistically both descriptive and inferential. The validity of mathematical problems was based on the expert assessment and validity test while the reliability was tested using product moment correlation. Pre-test and post-test data had been tested and both of them were homogeneous and normally distributed. The homogeneity test used Lavene test and the normality test used Chi Square. The influence test was performed using statistics, the average difference test, the two-way ANOVA test, and the Post Hoc follow-up test with Scheffe. All data were processed using SPSS. This study indicated the success by obtaining a significant value of 0.00 <α. Hence, it can be concluded that there is an effect of the implementation of PBL models and learning styles on mathematical problem-solving and self-esteem abilities.